Impact of Malaria Control on the Demand for ACTs - Laxminarayan, Ramanan; Klein, Eili; Smith, David (World Bank, Washington, DC, 2013)
As planning for malaria shifts from control to elimination and eventual eradication, policymakers are faced with decisions about resource allocation, and best approaches for financing malaria control interventions. At the operational level, these decisions will determine the relative emphasis on different tools such as insecticide treated nets (ITNs), indoor residual spraying (IRS) and artemisinin-based combinations (ACTs) in various local settings. At a global level, these decisions will guide the appropriate role of global financing mechanisms such as the Affordable Medicines Facility for Malaria (AMFm) in the malaria elimination effort. Previous papers have separately examined the cost-effectiveness of individual tools like IRS and ITNs and financing mechanisms such as the AMFm. Here we look at the cost-effectiveness of AMFm at different transmission intensities and levels of malaria control. We find that deaths averted as a result of AMFm are maximized when other control measures such as ITNs are simultaneously applied. Although policymakers have to tradeoff between investments in AMFm and malaria prevention tools, our results indicate strong synergies that get stronger as malaria control is amplified.